Patrilocality and hunter-gatherer-related ancestry of populations in East-Central Europe during the Middle Bronze Age - Chyleński, Maciej; Makarowicz, Przemysław; Juras, Anna; Krzewińska, Maja; Pospieszny, Łukasz; Ehler, Edvard; Breszka, Agnieszka; Górski, Jacek; Taras, Halina; Szczepanek, Anita; Polańska, Marta; Włodarczak, Piotr; et al. (Nature communications, 2023)
The demographic history of East-Central Europe after the Neolithic period remains poorly explored, despite this region being on the confluence of various ecological zones and cultural entities. Here, the descendants of societies associated with steppe pastoralists form Early Bronze Age were followed by Middle Bronze Age populations displaying unique characteristics. Particularly, the predominance of collective burials, the scale of which, was previously seen only in the Neolithic. The extent to which this re-emergence of older traditions is a result of genetic shift or social changes in the MBA is a subject of debate. Here by analysing 91 newly generated genomes from Bronze Age individuals from present Poland and Ukraine, we discovered that Middle Bronze Age populations were formed by an additional admixture event involving a population with relatively high proportions of genetic component associated with European hunter-gatherers and that their social structure was based on, primarily patrilocal, multigenerational kin-groups.
Keywords: Poland; Polsko; Europe; Genome, Human; Humans; lidé; Human Migration; sociální změna; dějiny starověku; History, Ancient; migrace lidstva; genom lidský; Evropa; Social Change